ANALISIS METODE PENGUJIAN PERANGKAT LUNAK BLACKBOX TESTING DAN PEMODELAN DIAGRAM UML PADA APLIKASI VETERINARY SERVICES YANG DIKEMBANGKAN DENGAN MODEL WATERFALL - Muhamad Syarif; Eri Bayu Pratama (STMIK KAPUTAMA, 2021)
Current technological developments can facilitate work in various fields, one of the information systems that need to apply computer technology is in the health sector. Veterinary services produce medical records which are an important component of important patient records that must be managed properly and should be accessed quickly. To develop a computerized system, you must use the right software development model where the waterfall model is one of the models that is often used, the results of the software that has been developed need to be tested before being implemented. Blackbox testing and use in the waterfall phase is considered to reduce the incidence of errors in functionality.